ln (2x-1) = 3

We coudl rewrite ln x=y as x= e^y

==> 2x-1 = e^3

Now add 1 to both sides:

==> 2x = e^3 + 1

Now divide by 2:

==> x = (e^3 + 1)/2

==> **x = 10.54 (approx.)**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now